Big data and its impact on IT consultancy - Mohamed, Habab; Md Hasim, Nur Nadiah; Zangirova, Alfiya; Ibrahim, Jamaludin (Research Publish Journals, 2016)
This paper discusses some of the areas which encompass big data and its adoption within Information Technology (IT) consultancy and professional practice. Among the issues that are highlighted in this paper are the relation of big data and its relevancy to IT consulting practice, why big data is increasingly getting and being in the spotlight and how it impact businesses. Undoubtedly, big data technology enables businesses to seek new opportunities and help managers in organizational decision-making. The advisory from IT consultants’ emphasis on what businesses need to get, and that is an expert’s insight before they truly understand and adopt big data and making investments on this on demand technology, as there are some challenges and issues in regards to big data that businesses need to be aware of and ready for.